The Role of Khoja Yusuf Hamadani's Spiritual Heritage In The Development of The History of Bukhara Sufism - Kurbanovich, Barnoev (Indonesian Journal Publisher, 2025)
Yusuf Hamadoniy's growing up among the people, his ideas and philosophical-social views, suggest that he was one of the progressive intellectuals of his time. His legacy as well as the upbringing of a new generation of specialists who study in greater depth the development of Eastern civilization and philosophical thought is a huge task ahead of us. In the religious-mystical views of Sheikh Yusuf Hamadani, new thoughts about God, man, nature, ideas have matured in moderate content and forms. They in turn had a strong spiritual and educational impact on the rise of the religious-mystical traditions of Abdulkholik Ghijduwani, Bahauddin Naqshband and others.This article discusses Yusuf Hamadoniy's role in the development of Sufism in Transoxiana, particularly Bukhara, and the significance of his spiritual heritage in the development of great Sufis in this region.